Vitreomacular Attachment Ultrastructure and Histopathological Correlation. (2nd August 2016) - Breazzano, Mark Philip; Fang, HengSheng; Robinson, Michael R.; Abraham, Jerrold L.; Barker-Griffith, Ann E.
ABSTRACT: Purpose : The ultrastructural anatomy of the vitreomacular interface in young human donor eyes and animal eyes is explored using scanning electron microscopy (SEM) to determine its relationship with the formation of the perimacular ridge from abusive head trauma, as well as macular hole formation, vitreomacular traction syndrome, and preretinal hemorrhage. Materials and methods : SEM is used to image the posterior poles of 23 human donor eyes, as well as several cow, dog, monkey, pig, and rabbit eyes for vitreomacular interface anatomy. We examined autopsy eyes from abusive head trauma histopathologically. Results : Two rings of thick, circumferential, vitreous attachment at the area centralis are found. An inner ring at the fovea, R1, and an outer ring at the perifoveal region, R2, are both observed in eyes from donors < 30 years of age; comparatively, in eyes from donors > 30 years, only R2 is present ( p <0.001). R2 is found with unique elliptical shape in Cynomolgus monkey. Macula, R1, and R2 are not detected in cow, dog, pig, or rabbit eyes. Conclusions : The vitreomacular ring attachments found in donor eyes correspond anatomically with the perimacular ridge found histopathologically in abusive head trauma, and likely correlates with the macular hole, vitreomacular traction syndrome, and preretinal hemorrhage. Vitreomacular interface anatomy in the monkey, but not the cow, dog, pig, or rabbit, demonstrates some anatomical similarity to that of the human, consistent with species differences regarding the area centralis.